Biochemical Defense Response: Characterizing the Plasticity of Source and Sink in Spring Wheat under Terminal Heat Stress - Kumar, Ranjeet R.; Goswami, Suneha; Shamim, Mohammed; Mishra, Upama; Jain, Monika; Singh, Khushboo; Singh, Jyoti P.; Dubey, Kavita; Singh, Shweta; Rai, Gyanendra K.; Singh, Gyanendra P.; Pathak, Himanshu; et al. (Frontiers in Plant Science, 2017)
Wheat is highly prone to terminal heat stress (HS) under late-sown conditions. Delayed- sowing is one of the preferred methods to screen the genotypes for thermotolerance under open field conditions. We investigated the effect of terminal heat stress on the thermotolerance of four popular genotypes of wheat i.e. WR544, HD2967, HD2932 and HD2285 under field condition. We observed significant variations in the biochemical parameters like protein content, antioxidant activity, proline and total reducing sugar content in leaf, stem, and spike under normal (26±2ºC) and terminal HS (36±2ºC) conditions. Maximum protein, sugars and proline was observed in HD2967, as compared to other cultivars under terminal HS. Wheat cv. HD2967 showed more adaptability to the terminal HS. Differential protein-profiling in leaves, stem and spike of HD2967 under normal (26±2°C) and terminal HS (36±2°C) showed expression of some unique protein spots. MALDI-TOF/MS analysis showed the DEPs as RuBisCO (Rub), RuBisCO activase (Rca), oxygen evolving enhancer protein (OEEP), hypothetical proteins, etc. Expression analysis of genes associated with photosynthesis (Rub and Rca) and starch biosynthesis pathway (AGPase, SSS and SBE) showed significant variations in the expression under terminal HS. HD2967 showed better performance, as compared to other cultivars under terminal HS. SSS activity observed in HD2967 showed more stability under terminal HS, as compared with other cultivars. Triggering of different biochemical parameters in response to terminal HS was observed to modulate the plasticity of carbon assimilatory pathway. The identified DEPs will enrich the proteomic resources of wheat and will provide a potential biochemical marker for screening wheat germplasm for thermotolerance. The model hypothesized will help the researchers to work in a more focused way to develop terminal heat tolerant wheat without compromising with the quality and quantity of grains.